Analysis and study of Future atmospheric hazards in Sistan region - Neamatallah Safarzaei; Alireza Entezari; Mokhtar Karami; Gholamali Khammar (تحقیقات کاربردی علوم جغرافیایی)
Today climate change cause increase in concentration of greenhouse gases has been cause increase extreme events and atmospheric hazards. goal of this research, analyze and review climate future is for atmospheric hazards in sistan region. In this study, to simulate minimum and maximum temperature data used from model data CanESM2 under three scenarios (RCP2.6, RCP4.5, RCP8.5) with SDSM statistical scrolling and to simulate rainfall data from the Hadcm3 model under scenarios (A1B, A2, B1) with statistical scrolling LARS-WG. For this purpose, after calibration, validation and data modeling at the selected station, the performance of the model from the viewpoint of the compliance of the base temperature data (1984-2005) and rainfall (1986-2015) with simulation values (2020-2039) evaluated at a significant level of confidence. To adapt base data to simulated data Used of the three criteria root mean square error (RMSE), coefficient of determination (R2) and mean squared error (MSE). According to simulated data were examined four important atmospheric hazard frost, heat waves, extreme precipitation and drought. The results showed that heat waves and drought in the future are serious threats in the region So that in 2021, under release scenario RCP 2.6, Predicted 32 heat waves and the study area will experience more than five heat waves in the year. In addition, most frequent drought forecast in 2020, under release scenario A1B. Extreme precipitation in some years under scenario B1 can be significant threat in the region. Intensity and abundance annual frost under release scenario RCP2.6 more than other scenarios and lower relative to investigated atmospheric threats.